The indirect NMDAR antagonist acamprosate induces postischemic neurologic recovery associated with sustained neuroprotection and neuroregeneration - Doeppner, Thorsten Roland; Pehlke, Jens; Kaltwasser, Britta; Schlechter, Jana; Kılıç, Ertuğrul; Baehr, Mathias; Hermann, Dirk Matthias (Nature Publishing Group, 2015)
Cerebral ischemia stimulates N-methyl-D-aspartate receptors (NMDARs) resulting in increased calcium concentration and excitotoxicity. Yet, deactivation of NMDAR failed in clinical studies due to poor preclinical study designs or toxicity of NMDAR antagonists. Acamprosate is an indirect NMDAR antagonist used for patients with chronic alcohol dependence. We herein analyzed the therapeutic potential of acamprosate on brain injury, neurologic recovery and their underlying mechanisms. Mice were exposed to cerebral ischemia, treated with intraperitoneal injections of acamprosate or saline (controls), and allowed to survive until 3 months. Acamprosate yielded sustained neuroprotection and increased neurologic recovery when given no later than 12 hours after stroke. The latter was associated with increased postischemic angioneurogenesis, albeit acamprosate did not stimulate angioneurogenesis itself. Rather, increased angioneurogenesis was due to inhibition of calpain-mediated pro-injurious signaling cascades. As such, acamprosate-mediated reduction of calpain activity resulted in decreased degradation of p35, increased abundance of the pro-survival factor STAT6, and reduced N-terminal-Jun-kinase activation. Inhibition of calpain was associated with enhanced stability of the blood-brain barrier, reduction of oxidative stress and cerebral leukocyte infiltration. Taken into account its excellent tolerability, its sustained effects on neurologic recovery, brain tissue survival, and neural remodeling, acamprosate is an intriguing candidate for adjuvant future stroke treatment.
WOS: 000365891300021
PubMed ID: 26219600
Keywords: Animal Models; Casic Science; Brain Ischemia; Excitotoxicity; Focal Ischemia; Neuroregeneration